Risks Associated with Cockroach Periplaneta Americana as a Transmitter of Pathogen Agents - Y.Al-bayati, Nagham; Shakir Al-Ubaidi, Anfal; K. Al-Ubaidi, Israa (Diyala Journal of Medicine, 2019)
Objective: To determine the possible role of cockroaches as a transmitter of medically important microorganisms, pathogenic organisms were isolated and identified from external and guts of cockroaches trapped at hospitals and houses. Methods: One hundred and fifty two cockroaches were collected from different parts of hospital and houses around it. They were collected for isolation and identification of bacteria and parasites from external surface and internal digestive tract of cockroaches. Statistical analysis was done by using t- test. Results: This study show that high rates of cockroaches show contamination of medically important bacteria and parasites. The species of the pathogenic agents was determinate and the number and percentages of infected cockroaches was recorded. Conclusion : And for this, cockroaches act as a potential transmitter of medically important pathogenic and may cause of nosocomial infection in both hospitals and houses. Therefore, control of cockroaches will substantially minimize the spread of infectious diseases in our environment.